The Dissolved Oxygen Sensor Design Based on Ultrasonic Self-Adaption and Self-Cleaning. (3rd July 2020) - Xiao, Zhong; Wang, Jingtong; Yi, Chen; Wang, Zairong; Wang, Liang
Abstract : Dissolved oxygen sensor is the key of dissolved oxygen measurement and it is usually implemented by electrochemical method, which measures dissolved oxygen content by the diffusion rate of molecular oxygen through film. However, the film on the electrochemical sensor probe is most likely to be blocked up by the waterborne contaminant, which may reduce the service life of the sensor and the indirect influence on the sensor's current. This is caused by changes of water temperature, which may lead to the decline in the accuracy of the sensor's output. This paper suggests a new method to implement the intelligent dissolved oxygen sensor. Our method mainly aims at ultrasonic automatic cleaning, automatic adjustment, and adaptation for the changes of temperature, which can not only regularly clean the dissolved oxygen sensor probe but also automatically calibrate the instruments based on the changes of temperature by combining software and hardware. The experiments show that the ultrasonic cleaning technology can not only increase the service life of the sensor by cleaning the film on the probe safely and effectively but also improve the accuracy of the sensor's output. Our method also has the advantages of simple structure, high accuracy of measurement, long service life, convenience, and stability, which is suitable for application and popularization.